2016
DOI: 10.1016/j.alcohol.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

β-endorphin regulates alcohol consumption induced by exercise restriction in female mice

Abstract: Animal models have long been used to study the mechanisms underlying the complex association between alcohol and stress. Female mice prevented from running on a home-cage activity wheel increase voluntary ethanol consumption. β-endorphin is an endogenous opioid involved in negatively regulating the stress response and has also been implicated in the risk for excessive drinking. The present study investigates the role of β-endorphin in moderating free-choice consumption of ethanol in response to a blocked activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…We previously observed increased adrenal gland weight in β-E deficient mice following EtOH exposure (Grisel et al 2008;McGonigle et al 2016) but did not explore basal or sex differences. Therefore, immediately following the BT on day 4, the left and right adrenal glands were harvested and total adrenal weight (normalized by body weight, g/kg) was calculated and is summarized in Fig.…”
Section: * -E -/--E +/-Females Malesmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously observed increased adrenal gland weight in β-E deficient mice following EtOH exposure (Grisel et al 2008;McGonigle et al 2016) but did not explore basal or sex differences. Therefore, immediately following the BT on day 4, the left and right adrenal glands were harvested and total adrenal weight (normalized by body weight, g/kg) was calculated and is summarized in Fig.…”
Section: * -E -/--E +/-Females Malesmentioning
confidence: 99%
“…Moreover, CRH signaling in the extended amygdala-comprised the nucleus accumbens shell (NAc), bed nucleus of the stria terminalis (BNST) and central nucleus of the amygdala (CeA)-mediates binge-like EtOH consumption (Lowery-Gionta et al 2012;Pleil et al 2015;Rinker et al 2017), and we recently observed increased Crh mRNA in the extended amygdala of β-E À/À female mice (McGonigle et al 2016). Therefore, we hypothesized that binge-like drinking is regulated by sex and β-E through alterations in Crh expression and glucocorticoid secretion affecting stress circuitry and anxiety-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…During both 2BC and DID, female, but not male, C57BL/6J mice increased their alcohol consumption and preference when their running wheels were locked, again substantiating the idea that female mice may be using wheel running as a substitute for alcohol consumption . Finally, McGonigle et al examined the effect of intermittent wheel access on DID (20% alcohol) using female C57BL/6J, β‐endorphin knock‐out (βE‐KO) and β‐endorphin heterozygote (βE‐HT) mice. Both βE‐KO and βE‐HT significantly increased their alcohol consumption when wheel running was prevented.…”
Section: Behavioral Models Investigating the Interaction Between Wheementioning
confidence: 92%
“…Numerous studies in rodents have provided evidence for an interaction between voluntary wheel running and alcohol consumption . In a recent review, Hallgreen et al pointed out that, “physical exercise is widely regarded as “medicine” for the prevention and treatment of myriad somatic health conditions.” However, the effectiveness of physical activity to treat AUDs remains understudied.…”
Section: Behavioral Models Investigating the Interaction Between Wheementioning
confidence: 99%
See 1 more Smart Citation